Effectiveness Of Swaddle Bathing On Neonatal Stability In Premature Infants: A Literature Review - Iftichori, Rania; Suci Ramanda Sari; Sabrina Eka Apriyanti; Regina Natalia (Jurnal Ilmiah Ners Indonesia, 2026)
Premature infants are susceptible to stress and homeostasis disorders due to physiological immaturity. One routine care procedure that can be a stressor is bathing. Swaddling involves wrapping the infant in a towel and bathing them in warm water, while conventional bathing uses a wet washcloth. This study aims to evaluate the effectiveness of swaddling compared to conventional bathing in reducing stress and maintaining physiological stability in premature infants. The authors conducted a systematic literature search in Google Scholar and PubMed for randomized controlled trials (RCTs) and quasi-experimental studies on premature infants receiving swaddling and conventional bathing interventions. Ten articles were selected that met the criteria for further analysis. The results of the swaddle bath intervention studies consistently showed significant advantages in maintaining body temperature (mean post-bath 36.8°C), stabilizing heart rate and respiration, and reducing crying duration by up to 60% compared to conventional bathing (p<0.05). In addition, this technique increased infant comfort and minimized energy expenditure due to stress. Swaddling bathing is an effective, safe, and developmental care-oriented intervention. This method is recommended as standard practice in the care of premature infants in the NICU.